The Effects of the TPACK-P Educational Program on Teachers’ TPACK: Programming as a Technological Tool - Won Kim, Seong; Lee, Youngjun (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study examined the effects of introducing programming as a technological tool for teachersâ€™ Technological Pedagogical Content Knowledge (TPACK) development.Methods/Statistical Analysis: Thirty-two teachers were divided into two groups, completing different types of TPACK educational programs. The control groupâ€™s TPACK training program was based on information and communication technology (ICT), while that of the experimental group was based on programming. To verify the effectiveness of the TPACK training program, tests were administered before and after the educational program. A statistical analysis of questionnaire results also investigated changes resulting from TPACK.Findings: Both the control and experimental groups showed statistically significant improvements in the post-test compared with the pre-test. However, in the detailed areas of TPACK by group, the improvements in the two groups differed. Unlike the control group, the experimental group showed a statistically significant improvement in the knowledge related to technology. This result illustrated that programming is effective in solving the problem of integrating technology into the classroom. In contrast, there was no significant difference in the post-test, as this was applied in the short term. However, programming has been shown to affect Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), and TPACK. In summary, the results showed that a TPACK educational program based on programming is effective for teachersâ€™ TPACK development.Â Keywords: TPACK, In-service teacher, Programming, TPACK-P, Educational program